A novel system for reducing CO2-crude oil minimum miscibility pressure with CO2-soluble surfactants. (1st December 2020) - Zhang, Chao; Xi, Linghui; Wu, Pingkeng; Li, Zhaomin
Graphical abstract: Highlights: A novel system for reducing CO2 /oil MMP is proposed by using CO2-soluble surfactants. A new IFT measurement method is performed to investigate CO2 /oil interface behavior. The solubility and partition coefficient of surfactants are also studied. The synergy mechanisms of surfactant and ethanol for MMP reduction are thus proposed. Abstract: Due to its lower viscosity and thus better injectivity than water, CO2 injection has attracted lots of attention in tight oil recovery. Lowering the minimum miscible pressure (MMP) of CO2 and crude oil for an easier realization of the miscible condition where crude oil is displaced the most efficiently by CO2 is critical in CO2 injection. However, the limited solubilities of most surfactants in CO2 impose difficulties in reducing the MMP as surfactants can hardly in presence at the interface to lower the interfacial tension (IFT). In this work, we overcome this limitation by introducing ethanol as a co-solvent to notably promote the solubilities of four different surfactants (NP-9, 2EH-PO5 -EO9, AOT, and TXIB) in CO2 . As a consequence of the enhanced solubilities, the surfactants reduce more efficiently the CO2 -crude oil IFT and MMP. Systematical measurements of CO2 -crude oil IFT are conducted to distinguish the efficiencies of the four surfactants with and without ethanol as co-solvent. Based on the measured IFT, solubilities, and partition coefficients of the surfactants in CO2 and crude oil, a mechanistic understanding of the synergy between ethanol and surfactants are proposed. Under the optimal conditions of 7 wt% ethanol and 0.3 wt% TXIB, the MMP of crude oil and CO2 can be reduced as much as 30.2%. The remarkable reduction of MMP is very intriguing and will be highly beneficial in tight oil recovery.